2017
DOI: 10.1093/eurheartj/ehx342
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbe-generated metabolite trimethylamine-N-oxide as cardiovascular risk biomarker: a systematic review and dose-response meta-analysis

Abstract: This is the first systematic review and meta-analysis demonstrating the positive dose-dependent association between TMAO plasma levels and increased cardiovascular risk and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

21
322
6
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 437 publications
(355 citation statements)
references
References 44 publications
21
322
6
6
Order By: Relevance
“…2 Recent animal and human data in PCOS showed alterations in composition of gut microbiota in PCOS, partly associated with androgen excess. [13][14][15] Even though limited studies have reported dysbiosis in PCOS, to the best of our knowledge, no data are available on gut microbiota-derived metabolites and impact of any treatment on those in the syndrome. 8,9 Trimethylamine N-oxide (TMAO) is the most well-known gut microbiota-related cardiometabolic risk factor which is highly related to atherosclerotic cardiovascular disease, type 2 diabetes and gestational diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Recent animal and human data in PCOS showed alterations in composition of gut microbiota in PCOS, partly associated with androgen excess. [13][14][15] Even though limited studies have reported dysbiosis in PCOS, to the best of our knowledge, no data are available on gut microbiota-derived metabolites and impact of any treatment on those in the syndrome. 8,9 Trimethylamine N-oxide (TMAO) is the most well-known gut microbiota-related cardiometabolic risk factor which is highly related to atherosclerotic cardiovascular disease, type 2 diabetes and gestational diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated circulating concentrations of both TMAO and its precursors are associated with increased risk of adverse cardiovascular events, independently of traditional risk factors. [13][14][15] Even though limited studies have reported dysbiosis in PCOS, to the best of our knowledge, no data are available on gut microbiota-derived metabolites and impact of any treatment on those in the syndrome. The primary aim of this study was to determine whether microbiota-related cardiometabolic risk markers are altered in PCOS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity is one of the most important predictors of CVD and T 2 DM, and from an etiologic point of view, it is important to elucidate whether the associations between TMAO and CVD or other NCDs are established via an independent association between TMAO and obesity as a prognostic cardio‐metabolic risk factor. While no summarized evidence regarding the associations between obesity and TMAO is available, there are several meta‐analyses regarding the association between increased TMAO levels and risk of CVD mortality and T 2 DM . It should also be noted that no study is available to summarize the association between TMAO and obesity measurements.…”
Section: Introductionmentioning
confidence: 99%
“…19 It is also known from epidemiological studies that specific methylated amines are associated with the risk for cardiovascular diseases, for instance ADMA 20,21 or TMAO. [22][23][24][25] TMAO is also a striking example of the recently recognized importance of the gut microbiota for foodrelated health issues. 26,27 In summary, this compound class is of high relevance and an interesting target for all studies related to nutrition, physical activity, and health.…”
mentioning
confidence: 99%